PENGARUH PEMBERIAN TEPUNG KUNYIT (CURCUMA DOMESTICA VAL.) DALAM RANSUM TERHADAP PERFORMANS PRODUKSI ITIK (ANAS SPP) PERIODE BERTELUR - Nuun Marfuah Toana (Universitas Tadulako, 2008)
The research aim was to study the effect of turmeric flour additions on duck productivity performance during layer period. The research was in a traditional farm owned by the local community of Biromaru Village, Sigi Biromaru sub-district from 5 October 2007 to 12January 2008. Twenty five male layer period ducks of CV 2000-INA 1400 type and of 1400 -1500 g initial weights were used.The experiment was designed in a Completely Randomized design with 5 different levels of turmeric flour added into the duck feed as the treatments. Each treatment was replicated five times. These treatments included 0, 2, 4, 6 and 8 percent of curcuma flour in feed at the same feed protein equivalent to 17 % and energy 2900 kkal/kg.Parameter observed were feed consumption, egg weight and efficiency of feed consumption which all showed to be insignificantly affected by the treatments.